PENGEMBANGAN APLIKASI PENDAFTARAN AKUN EMAIL MICROSOFT 365 DAN GOOGLE WORKSPACE BERBASIS LARAVEL DAN REACT DI POLITEKNIK PIKSI INPUT SERANG - Muhammad Khaidir Fahram; Vina Vijaya Kusuma2 (Journal of Innovation And Future Technology, 2025)
The creation of institutional email accounts such as Microsoft 365 and Google Workspace is often manually handled by administrators, resulting in inefficiencies and potential data errors. This study aims to design and develop a secure and integrated web-based email registration application. The application is built using Laravel 12 for the backend and React (TypeScript) with Inertia.js and radix-ui for the frontend. The system integrates with the Microsoft Graph API and Google Admin SDK for automated account creation, and with the WhatsApp API for user notifications. In terms of security, the system employs middleware for access control, conditional validation based on user roles (NIM for students, NIDN for lecturers), temporary password encryption using Laravel Crypt, form protection via reCAPTCHA, and rate limiting to prevent abuse. Testing results show that the system improves efficiency, accuracy, and security in the institutional email registration process at Politeknik Piksi Input Serang.